RAGAM LAKON PERAN AUDITOR DALAM PEMERIKSAAN BANSOS HIBAH - Anggun Anita Sari; Zaenal Fanani (Jurnal Akuntansi Aktual, 2018)
This study aims to describe how the reality of the role of internal auditors of local government in carrying out the task of social assistance and grant audit. The internal auditor of the government is considered merely to waive its obligations. Implementation of social assistance and grants has always been an important notice of BPK in its Opinion of the Local Government Financial Report Indraprasta. Using the methodology of phenomenology, the results of this study found that there is a role implementation stated as a "justifier" in which Herman prioritizes a neat accountability report rather than on-site implementation. The second role implementation refers tp "avoidance" in the examination of cases that received attention solely to maintain the idealism and integrity. The third role is considered as a "safety" that is securing local finance. Lasty, auditors have role to "provide solutions".